FAMILY HYBOTIDAE - Ale-Rocha, Rosaly; de Freitas-Silva, Rafael Augusto Pinheiro (Zootaxa, 2016)
Hybotidae is a diverse family of the order Diptera, suborder Brachycera, superfamily Empidoidea. Hybotid flies are generally yellow to black, are morphologically diverse, and are distributed worldwide. The monophyly of the family is based on: palpifer and fore tibial gland present, laterotergite bare and R4+5 unbranched. Hybotids are mainly predators and are usually found on the vegetation, logs and other surfaces, or in flight during displacement and forage. This catalogue, based on the study of specimens and available literature records, summarizes and updates the information on the Colombian fauna of Hybotidae, which includes 19 species distributed in six genera.